The world is burning: What exactly are firebrands and why should anyone care? - Manzello, Samuel L.; Suzuki, Sayaka (Frontiers in Mechanical Engineering, 2023)
Large outdoor fires have become commonplace all over the world. The International Organization for Standardization (ISO) defines large outdoor fires as an urban fire, tsunami-generated fire, volcano-generated fire, wildland-urban interface (WUI) fire, wildland fire, or informal settlement fire, where the total burnout area is significant. Perhaps of all the large outdoor fires, it is wildland fires that spread into urban areas, simply called WUI fires that attract the most attention. A glance at the recent headlines in the summer of 2022 reveals numerous catastrophic WUI fires all over Europe. Across the Atlantic Ocean in the USA, there is yet another destructive WUI fire raging in the USA state of California. With the increasing risks from a changing climate, these large outdoor fire disasters are only going to become more and more commonplace all over the world. More homes will be lost and more lives will be lost. It is the authors opinion that a targeted, multi-disciplinary approach is needed to address the large outdoor fire problem. In this short, invited paper to Horizons in Mechanical Engineering, it is argued that large outdoor fire problem is a fascinating and challenging research area and that engineers have the necessary skills and training to impact a problem that influences millions upon millions of people all over the world. An important danger, present in all large outdoor fires, are firebrands. Firebrands are introduced for non-specialist readers, and the most recent literature is reviewed. Several challenges are discussed, in particular, areas where engineers may help move the needle forward on this globally important topic.